Animal-Based Welfare Assessment of Cattle and Water Buffalo in Bangladeshi Slaughterhouses. Issue 2 (2nd April 2020) - Alam, Mohammad Rashedul; Islam, Md. Jahirul; Amin, Al; Shaikat, Amir Hossan; Pasha, Md. Ridoan; Doyle, Rebecca E.
ABSTRACT: This study quantified the welfare of 423 cattle and water buffalo in four Bangladeshi slaughterhouses to identify facility and species-specific factors that influence welfare. The majority of animals arrived at the slaughterhouse with injuries, signs of dehydration and oculo-nasal discharge. During slaughter, buffalo experienced more stabbing at the throat (21%), compared to local cattle (10%, P = 0.011), and significantly more cuts to the neck during slaughter (5.1 ± 1) than Hariana (3.9 ± 1) or local cattle (3.6 ± 1.1; P < 0.001). These results indicated that welfare compromise is common to all species, but that the risk to buffalo was greater. Partial severing of carotid arteries was common and affected time to unconsciousness. There was a statistical interaction between facility and species on the time taken for animals to reach unconsciousness, suggesting that welfare within a location could be improved; however, animal welfare was compromised at all facilities. Immediate welfare improvements could be made by training for effective halal slaughter, and future welfare improvements could be gained by improved facility infrastructure for restraint and halal approved pre-slaughter stunning.